Moving Forward Charting the Much-Needed Evolution of the Digital Services Act - Papp János Tamás (HUNGARIAN YEARBOOK OF INTERNATIONAL LAW AND EUROPEAN LAW, 2024)
The Digital Services Act (DSA) represents a pivotal step in the evolution of internet governance, aiming to address several critical issues that have emerged in the digital era. This article delves into the potential pathways through which the DSA could evolve to tackle three significant challenges currently facing the online world: contractual content moderation and fundamental rights, algorithmic transparency and the opt-out system, and the complexities of disinformation and the codes of conduct. (i) Firstly, the article explores the nuanced approach of the DSA towards contractual content moderation, emphasizing its minimal intervention in the substantive content of user-platform contracts. This section discusses how the DSA’s focus on procedural regulation rather than substantive contract terms could impact fundamental rights and the autonomy of platform operators in defining their terms of service. (ii) Secondly, the discussion shifts to the issue of algorithmic transparency and user autonomy in an increasingly automated digital environment. It criticizes the DSA’s current measures and suggests how enhanced transparency and a more robust opt-out system could empower users while addressing the challenges posed by the opacity of algorithmic decision-making. Lastly, the article addresses the handling of disinformation within the DSA framework, analyzing its current approach and proposing more stringent measures to combat the spread of false information effectively. This section evaluates the potential of codes of conduct as flexible, adaptive tools to improve content moderation practices and mitigate systemic risks posed by disinformation.